Rationale for the Bihar Curriculum Framework and the Process of Drafting: Education for Equity, Harmony and Excellence - Kantha, Vinay K. (Voices of Teachers and Teacher Educators, 2018)
As a follow up of the National Curriculum Framework-2005, the Bihar Curriculum Framework (BCF)-2006/2008 was brought out. This article narrates the reason behind making of the BCF and also details out the process perspective of BCF which is now a guiding document for the school education in the state of Bihar.